1999
DOI: 10.1002/1531-8249(199906)45:6<742::aid-ana8>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataracts facial dysmorphism neuropathy syndrome, a novel complex genetic disease in Balkan gypsies: Clinical and electrophysiological observations

Abstract: During a study of hereditary motor and sensory neuropathy‐Lom in Bulgaria, a previously unrecognized neurological disorder was encountered, mainly in Wallachian Gypsies, who represent a relatively recent genetic isolate. The disorder has been termed the congenital cataracts facial dysmorphism neuropathy (CCFDN) syndrome to emphasize its salient features. Fifty individuals from 19 extended pedigrees were identified and examined clinically and electrophysiologically. At least 1 patient from each family was admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…The view that intermodal attention operates early is consistent with imaging studies reporting modulation of sensory cortices with intermodal attention (Tournev et al, 1999; Woodruff et al, 1996) but offers further information about the latency at which such modulations occur. The early latencies observed in the current study support the hypothesis that intermodal attention operates early in the sweep of sensory information to primary and secondary association cortices at latencies as early, or in some cases earlier, than has been reported with spatial attention manipulations.…”
Section: Discussionsupporting
confidence: 78%
“…The view that intermodal attention operates early is consistent with imaging studies reporting modulation of sensory cortices with intermodal attention (Tournev et al, 1999; Woodruff et al, 1996) but offers further information about the latency at which such modulations occur. The early latencies observed in the current study support the hypothesis that intermodal attention operates early in the sweep of sensory information to primary and secondary association cortices at latencies as early, or in some cases earlier, than has been reported with spatial attention manipulations.…”
Section: Discussionsupporting
confidence: 78%
“…It is characterized by the obligate signalling trias of bilateral congenital cataract, developmental delay and later demyelinating neuropathy [1]. Congenital bilateral cataract is the first and invariable presenting sign [2]. Other ocular manifestations are also possible such as microcornea, microphthalmia, micropupil and floppy eyelid [3].…”
Section: Introductionmentioning
confidence: 99%
“…Varon et al [7] observed an abnormal product in all cell types studied, regardless of their involvement in the clinical phenotype which results in a premature stop codon. The syndrome has been described exclusively in patients of Gypsy ancestry [2,7]. An original description from 1999 reported 50 patients from 19 families from Bulgaria [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital cataracts facial dysmorphism neuropathy syndrome (CCFDN, MIM: 604168) is a rare autosomalrecessive disorder, caused by the IVS6+389C>T mutation in the CTDP1 gene in patients of Gypsy ancestry [1,2]. Recurrent parainfectious rhabdomyolysis may be an integral part of the CCFDN phenotype [3], which has not attracted sufficient attention and may often be overlooked.…”
Section: Introductionmentioning
confidence: 99%